The Interactive Effects of Race and Expert Testimony on Jurors’ Perceptions of Recanted Confessions - Ewanation, Logan; Maeder, Evelyn M. (Frontiers in Psychology, 2021)
We examined the effect of defendant race and expert testimony on jurors’ perceptions of recanted confessions. Participants (591 jury-eligible community members) read a first-degree murder trial transcript in which defendant race (Black/White) and expert testimony (present/absent) were manipulated. They provided verdicts and answered questions regarding the confession and expert testimony. When examining the full sample, we observed no significant main effects or interactions of defendant race or expert testimony. When exclusively examining White participants, we observed a significant interaction between expert testimony and defendant race on verdicts. When the defendant was White, there was no significant effect of expert testimony, but when the defendant was Black, jurors were significantly more likely to acquit when given expert testimony. These findings support the watchdog hypothesis, such that White jurors are more receptive to legally-relevant evidence when the defendant is Black.